Platón, la República, y el anarquismo. Sobre el significado político del símil de la línea (Rep. 509 d-511e) - Ledesma Pascal, Felipe (Logos. Anales del Seminario de Metafísica, 2002)
This paper tries to undertake one more time the well-know image of the divided line to take out its political meaning by situating it in its context: a dialogue in which the justice is inquired. But it has at once the intention to intepret the question: what is justice? Not only as a moral or political question, but also as ontological, the question for that that makes posible every delimitation and every discernment. The place where both topics converge is the pólis, the place where the absence of principle, of arkhé, rest alive.